Life Cycle Assessment for desalination: A review on methodology feasibility and reliability - Zhou, Jin (2014)
As concerns of natural resource depletion and environmental degradation caused by desalination increase, research studies of the environmental sustainability of desalination are growing in importance. Life Cycle Assessment (LCA) is an ISO standardized method and is widely applied to evaluate the environmental performance of desalination. This study reviews more than 30 desalination LCA studies since 2000s and identifies two major issues in need of improvement. The first is feasibility, covering three elements that support the implementation of the LCA to desalination, including accounting methods, supporting databases, and life cycle impact assessment approaches. The second is reliability, addressing three essential aspects that drive uncertainty in results, including the incompleteness of the system boundary, the unrepresentativeness of the database, and the omission of uncertainty analysis. This work can serve as a preliminary LCA reference for desalination specialists, but will also strengthen LCA as an effective method to evaluate the environment footprint of desalination alternatives.